Decision Support System for Determining Marketing Strategy Using SWOT and AHP Methods - Prabukusumo, M. Azhar (Marqcha Institute, 2024)
In the competitive global business era, determining an effective marketing strategy is crucial for companies. This research integrates SWOT (Strengths, Weaknesses, Opportunities, Threats) and Analytic Hierarchy Process (AHP) methods to develop a decision support system in this context. The objective is to identify internal and external factors that affect the performance of manufacturing and service companies, and rank strategic priorities based on the relative weight of each SWOT factor using AHP. By analyzing case studies of several companies in the manufacturing and service industries, the results show that advanced production infrastructure and efficient supply chain management dominate as major internal strengths, while raw material price fluctuations and market competition as significant external threats. The implication is that international expansion strategies and improvements in digital service capacity are key in responding to current global market dynamics. This research not only provides new strategic insights for practitioners, but also provides a theoretical foundation for the development of more advanced analytical methodologies in corporate strategic analysis.